The Inhibition Activity of Tannin on the Formation of Mono-Species and Polymicrobial Biofilm Escherichia coli, Staphylococcus aureus, Pseudomonas aeruginosa, and Candida albicans - Hasyrul Hamzah; Triana Hertiani; Sylvia Utami Tunjung Pratiwi; Titik Nuryastuti (Faculty of Pharmacy, Universitas Gadjah Mada, 2019)
Biofilm acts as the mediator for infection nowadays. Approximately, more than 80% infection incidents are biofilm-formation related. Biofilm as bacteria's defense system is more difficult to eradicate by antibiotic; therefore, pathogen bacteria on their biofilm forms can make serious problems for human health. The invention of a new candidate for polymicrobial biofilm can be an essential challenge to be studied, in order to prevent infections related to biofilm. Tannin is a polyphenol compound with anti-bacterial and anti-fungal potential. This study aims to acknowledge the effectiveness of tannin in inhibition and degradation of C. albicans, P. aeruginosa, E. coli, S. aureus, and polymicrobial biofilm. The assay for biofilm inhibition and degradation were determined with microtiter broth method. The effectivity of tannin antibiofilm against polymicrobial biofilm were analyzed by calculating minimum biofilm inhibitory concentration (MBIC50) and minimum biofilm eradication concentration (MBEC50) values. The mechanism of action of tannin against polymicrobial biofilm was tested using scanning electron microscopy (SEM). The data were analyzed using the Statistical Package for the Social Sciences (SPSS) with a 95% confidence level. Tannin 1% gave inhibition activity of mono-species biofilm formation S. aureus in the middle phase and maturation of 79.04±0.01, 61.48±0.03, E. coli 74.56±0.01, 67.91±0.02, P. aeruginosa 67.32±0.05, 35.13± 0.01, C. albicans 60.62±0.01, 47.16±0.01. The results also provide evidence that tannin activity can degrade and damage the matrix of extracellular polymeric substance (EPS) polymicrobial biofilms. Hence, tannins can be a potential candidate for new antibiofilm for polymicrobial biofilm.